Faktor-Faktor yang Mempengaruhi Penemuan Penderita TB Paru di Kota Palu Provinsi Sulawesi Tengah - Awusi RYE, Yusrizal Djam’an Saleh2, Yuwono Hadiwijoyo (Berita Kedokteran Masyarakat (BKM), 2009)
Background:  Every  second Mycobacterium  tuberculosis  infected  1  person worldwide. Overall,  one-third  of the world’s population  is  currently  infected with  the TB  bacillus. 5%-10%  of  people who are  infected with  TB bacilli become  sick or  infectious at  some  time  during  their  life. Pulmonary TB  is  an  important  health problem  in worldwide. World Health Organization  (WHO)  recommended  controlling TB with DOTS  strategy since  1995. Focus of  global TB  control with DOTS strategy  is case  detection and  cure TB  patients. Case  detection  rate  in South East Asia is low (31%-54%) of the target global of CDR (70%). For the period 2006-2007 years CDR in Palu Municipalyti  is very  low  (34%-35%). Therefore,  it  is  important  to  find  factors  that  influence  for  case detection  of pulmonary  TB.Objectives: To  identify  the  relationship  between  independent  variables  of  knowledge,  length  of work, work load,  incentive,  training of DOTS, access,  service KIE  about TB  and screening  suspect TB with case  detection of pulmonary TBMaterial and Methods:  This was  an analytic  observational  study which used  a  cross  sectional  design with both quantitative  and qualitative  approaches. Subjects  of  the  study were  providers TB  program of Community Health Center  in Palu Municipality. Data were  descriptively  analyzed  (univariate)  and  statistically  analyzed (bivariate)  using  chi  square  test  and  logistic  regression  (multivariate)  at confident  interval 95%.and  significant level  5%.Results: Variables  that  have  significant  statistically  relationship  (p<  0.05) with  case detection  of pulmonary TB is screening suspect TB  (OR=8,92;      95%CI=2,36-38,65), service KIE about TB  (OR=8,85; 95%CI=2,16-36,97), training of DOTS  (OR=5,84; 95%CI=1,54-26,77).Conclusion: The  factors  to  have  significant  influence  of case  detection  pulmonary TB were screening  suspect TB,  service CIE  TB  and  training of DOTS. Screening  suspect TB was  the most  influencing  case detection  of pulmonary TB in Palu Municipality.Keywords:  case  detection of Pulmonary TB,  screening  of TB  suspect,  service CIE,  training  of DOTS, Palu municipality